Association of baseline vitamin D level with genetic determinants and virologic response in patients with chronic hepatitis B. Issue 3 (4th October 2017) - Yu, Rui; Tan, Deming; Ning, Qin; Niu, Junqi; Bai, Xuefan; Chen, Shijun; Cheng, Jun; Yu, Yanyan; Wang, Hao; Xu, Min; Shi, Guangfeng; Wan, Mobin; et al.
Abstract : Aim: The role of vitamin D in individuals with chronic hepatitis B (CHB) is unclear. We aimed to explore the association of baseline vitamin D level with genetic determinants and week‐104 treatment outcome in CHB patients. Methods: Baseline serum 25‐hydroxycholecalciferol (25(OH)D) levels and genetic polymorphism within GC, DHCR7, and CYP2R1 were determined in stored serum of 560 patients who were enrolled into a multicenter, randomized, controlled study and completed 104 weeks of telbivudine monotherapy or telbivudine‐based optimized therapy. Virologic response was defined as hepatitis B virus DNA <300 copies/mL (52 IU/mL) at week 104. Results: The mean 25(OH)D value was 29.64 ng/mL. The percentage of patients with vitamin D insufficiency (<30 ng/mL) and vitamin D deficiency (<20 ng/mL) were 55.0% and 20.9%, respectively. Gender, season, latitude, and GC rs2282679 polymorphism were independent factors of vitamin D status. Patients with sufficient vitamin D (≥30 ng/mL) achieved a higher virologic response rate than those with vitamin D insufficiency (81.7% vs. 67.2%, P < 0.001). The area under the curve of 25(OH)D to predict virologic response was 0.65 ( P < 0.001; 95% confidence interval, 0.62–0.67). On multivariate analysis, 25(OH)D level was an independent predictor of virologic response, but not associated with hepatitis B envelope antigen (HBeAg) seroconversion or alanine aminotransferase (ALT) normalization. Conclusions: Vitamin D insufficiency was highly prevalent in treatment‐naïve CHB patients in mainland China. Latitude and genetic determinants affect vitamin D status. Baseline vitamin D level can predict week‐104 virologic response, but not HBeAg seroconversion or ALT normalization.